2010
DOI: 10.1159/000317024
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Phantosmia: Outcome and Clinical Significance

Abstract: Background/Aim: Little is known about the clinical significance of phantosmia. The literature on phantosmia indicates that this symptom has a wide range of differential diagnoses. However, most cases of phantosmia remain of unknown origin. Our goal was to follow up patients with idiopathic phantosmia, with special regard to improvement rates and possible severe health conditions preceded by phantosmia of unknown origin. Methods: Forty-four patients with idiopathic phantosmia which had consulted our Ear-Nose-Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
0
24
0
2
Order By: Relevance
“…Reden et al [57] did, however, show that phantosmia has no prognostic significance in patients suffering from olfactory dysfunctions. In addition, Landis et al [58] concluded that idiopathic phantosmia does not seem to be a reliable predictor of severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reden et al [57] did, however, show that phantosmia has no prognostic significance in patients suffering from olfactory dysfunctions. In addition, Landis et al [58] concluded that idiopathic phantosmia does not seem to be a reliable predictor of severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Endpoints were primarily based on subjective patient responses. Management options included observation and medical and surgical therapy. No studies that met the inclusion criteria addressed the role of steroid therapy, and this may be the subject of future studies.…”
Section: Resultsmentioning
confidence: 99%
“…One article provided outcomes with observation alone, with 56.8% of patients reporting short‐term improvement of symptoms but only 31.8% of patients reporting long‐term relief (Table ). Twenty‐four patients were treated medically with antipsychotic medications, antiseizure medications, topical cocaine, or antimigraine prophylactic medications .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One group of investigators reported that what they described as “idiopathic phantosmia” disappeared spontaneously after the symptoms were present for a period of more than five years [123]. …”
Section: Introductionmentioning
confidence: 99%